Electricity storage device and method for producing metal compound particle group
Patent Information
- Application Number
- JP2020558398
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-11-22
- Filing Date
- 2019-11-18
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2039-11-18
AI Technical Summary
【0021】 本発明によれば、蓄電デバイスの内部抵抗の増加を抑制することができる金属化合物粒子群、金属化合物粒子群を含む蓄電デバイス用電極、および金属化合物粒子群の製造方法を提供することができる。
Smart Images

Figure 0007640265000003 
Figure 0007640265000004 
Figure 0007640265000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a metal compound particle group, an electrode for an electricity storage device, an electricity storage device, and a method for producing a metal compound particle group. [Background technology]
[0002] In recent years, the rapid spread of digital cameras, smartphones, and portable PCs has led to active development of secondary batteries. Secondary batteries are expected to be used for powering automobiles and storing electricity in smart grids in response to rising fuel prices and growing awareness of environmental impact.
[0003] The electrodes of the secondary battery include a positive electrode and a negative electrode containing an active material that reversibly absorbs and releases lithium ions, and an electrolyte solution with a lithium salt dissolved therein. In this lithium secondary battery, lithium ions are released from the positive electrode and absorbed into the negative electrode by charging and discharging, and lithium ions are released from the negative electrode and absorbed into the positive electrode by discharging. Lithium ion secondary batteries have the advantages of being able to operate at high voltages and having a large energy density.
[0004] Also, a so-called hybrid capacitor has been proposed to utilize the advantages of both lithium ion secondary batteries and electric double layer capacitors. The hybrid capacitor has a polarizable electrode having an electric double layer capacitance as a positive electrode and a metal compound particle capable of absorbing and releasing lithium as a negative electrode, and thus combines the advantages of both lithium ion secondary batteries and electric double layer capacitors. In other words, this hybrid capacitor has a high energy density and high input / output characteristics. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2015-189608 A Summary of the Invention [Problem to be solved by the invention]
[0006] When the metal compound particles used as electrode materials in these energy storage devices were used as negative electrode materials, deposits could form on the negative electrode during charging and discharging. These deposits are different from a film called SEI, and when they form, they cause an increase in internal resistance.
[0007] Therefore, an object of the present invention is to provide a metal compound particle group capable of suppressing an increase in the internal resistance of an electricity storage device, an electrode for an electricity storage device containing the metal compound particle group, and a method for producing the metal compound particle group. [Means for solving the problem]
[0008] In order to achieve the above object, the metal compound particle group according to this embodiment has the following configuration. (1) A metal compound particle group having a three-dimensional network structure in which metal compound particles are linked together, and a coating layer containing silicon oxide is formed on a part of the metal compound particle group.
[0009] (2) The coating layer containing silicon oxide may be formed on at least a portion of the surface of the metal compound particle.
[0010] (3) The amount of elemental silicon may be 0.4 to 3.0 wt % based on the total weight of the metal compound particles.
[0011] (4) The three-dimensional network structure may have voids, and the metal compound particles defining the voids may have a coating layer containing the silicon oxide formed thereon.
[0012] (5) The silicon oxide contained in the coating layer may be an amorphous silicon oxide.
[0013] (6) A pore volume change rate calculated from the pore distribution measured by nitrogen gas adsorption measurement of the metal compound particle group is 0.008 dV for a pore diameter of 10 nm or less. p / dr pThe pore volume change rate may be greater than 100%.
[0014] (7) The reduction rate of integrated intensity may be 25% or more relative to the metal compound particles on which the coating layer containing silicon oxide is not formed.
[0015] (8) The metal compound particles may be lithium titanate.
[0016] The metal compound particle group may be included in the electrode for an electricity storage device. Also, the metal compound particle group may be included in the electrode for an electricity storage device. The ...
[0017] The method for producing the metal compound particle group of this embodiment includes a mixing step of mixing the base metal compound particle group with a silicon oxide raw material, and a heating step of heating the powder obtained by the mixing step at 300 to 600°C.
[0018] The silicon oxide raw material may be mixed at a ratio of 1 to 20 wt % based on the weight of the base metal compound particle group.
[0019] The silicon oxide raw material may be mixed at a ratio of 3 to 20 wt % based on the weight of the base metal compound particle group.
[0020] In the mixing step, one or more kinds of alkali compounds may be further mixed. Alternatively, a pretreatment step of pretreating the base metal compound particles with an alkali compound may be included before the mixing step. Examples of the alkali compound include hydroxides, acetates, sulfates, carbonates, nitrates, and chlorides of alkali metals or alkaline earth metals, inorganic alkali agents, and organic alkali agents. Effect of the Invention
[0021] According to the present invention, it is possible to provide a metal compound particle group capable of suppressing an increase in the internal resistance of an electricity storage device, an electrode for an electricity storage device containing the metal compound particle group, and a method for producing the metal compound particle group. [Brief description of the drawings]
[0022] [Figure 1] FIG. 2 is a conceptual diagram showing a metal compound particle group of the present embodiment. [Diagram 2] 1 is an SEM image of a lithium titanate particle group of a comparative example, the magnification of which was 50.0K. [Diagram 3] 1 shows SEM images (×50.0K) of lithium titanate particle groups, where (a) is an SEM image of the lithium titanate particle groups of a comparative example, and (b) is an SEM image of the lithium titanate particle groups of an example. [Figure 4] 1 shows SEM images and graphs illustrating the results of elemental analysis of lithium titanate particle groups, where (a) shows the results for the lithium titanate particle groups of a comparative example, and (b) shows the results for the lithium titanate particle groups of an example. [Diagram 5] 1 is a graph showing the pore size distribution of a lithium titanate group of a comparative example. [Figure 6] 1 is a graph showing the pore size distribution of lithium titanate groups of Comparative Example and Example. [Figure 7] 1 is a graph showing the results of measuring the initial internal resistance of lithium ion secondary batteries having lithium titanate particle groups of a comparative example and an example prepared using a silane coupling agent having an acryloyl group in the negative electrode active material layer. [Figure 8] 1 is a graph showing the results of measuring the rate of increase in internal resistance after 2000 cycles for a lithium ion secondary battery containing lithium titanate particles of an embodiment prepared using a silane coupling agent having an acryloyl group in the negative electrode active material layer. [Figure 9] 1 is a graph showing the results of measuring the initial internal resistance of a lithium ion secondary battery having a negative electrode active material layer containing lithium titanate particle groups of a comparative example and an example produced using a silane coupling agent having an epoxy group. [Figure 10] 1 is a graph showing the results of measuring the rate of increase in internal resistance after 2000 cycles for lithium ion secondary batteries containing lithium titanate particle groups of a comparative example and an example prepared using a silane coupling agent having an epoxy group in the negative electrode active material layer. [Figure 11] 1 is a graph showing the results of measuring the initial internal resistance of lithium ion secondary batteries having lithium titanate particles of a comparative example and an example produced with the addition of an alkaline compound in an active material layer of a negative electrode. [Figure 12] 1 is a graph showing the results of measuring the rate of increase in internal resistance after 2000 cycles for lithium ion secondary batteries having lithium titanate particle groups of a comparative example and an example produced with the addition of an alkaline compound in the negative electrode active material layer. [Figure 13] Graphs showing the results of thermogravimetry performed on a lithium titanate particle group of a comparative example, where (a) is a graph of the thermogravimetry results, and (b) is a calibration curve for converting the amount of silane coupling agent from the amount of loss. [Figure 14] 1 is a graph showing the relationship between the amount of a silane coupling agent added and the amount of Si element contained in lithium titanate particle groups. [Figure 15] 5 is a graph showing the results of elemental analysis of the lithium titanate particle group of the example, where (a) is a graph showing the carbon concentration, (b) is a graph showing the silicon concentration, and (c) is a graph showing the carbon / silicon ratio. [Figure 16] 1 is a graph showing the results of X-ray photoelectron spectroscopy performed on lithium titanate particle groups before and after heat treatment. [Figure 17] 4 is a graph showing the results of X-ray diffraction analysis of the lithium titanate particle group after the heat treatment. [Figure 18] FIG. 1 shows the results of solid-state 1H-NMR measurement of lithium titanate particle groups of the comparative example and the example, where (a) is the measurement data of solid-state 1H-NMR, and (b) is a graph showing the calculation results of integrated intensity. [Figure 19]1 is a graph showing the results of measuring the rate of increase in internal resistance after 2000 cycles of lithium ion secondary batteries prepared using the lithium titanate particle groups of the comparative example and the example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] Hereinafter, embodiments of the present invention will be described. Note that the present invention is not limited to the embodiments described below.
[0024] [1. Configuration] The metal compound particle group is mainly used for electrodes of electricity storage devices. The metal compound particles constituting the metal compound particle group are materials that can function as a positive electrode active material or a negative electrode active material of electricity storage devices such as lithium ion secondary batteries and lithium ion capacitors. The metal compound particle group has a three-dimensional network structure in which nano-sized metal compound particles are linked together, and silicon oxide (SiO x Or SiO x (OH) 4-2X (x is 0 to 2) is formed on the metal compound particle. The coating layer containing silicon oxide is formed on at least a part of the surface of the metal compound particle. In addition, voids exist in the three-dimensional network structure of the metal compound particle group, and the coating layer containing silicon oxide is formed on the surface of the metal compound particle that defines the voids.
[0025] (Metal compound particle group) As shown in Figure 1, metal compound particle group A has a three-dimensional network structure. A three-dimensional network structure is a structure in which nano-sized metal compound primary particles 1 are bonded together to form a network, with nano-sized voids 2 present. There are no grain boundaries at the bonding interfaces of the primary particles 1, while numerous microscopic pores exist between the primary particles 1. In this metal compound particle group A, the three-dimensional network structure forms an electron path for the negative electrode active material, the voids 2 act as storage areas for the electrolyte, and the pores between the primary particles 1 act as paths for ions.
[0026] The metal compound particles are particles capable of absorbing and releasing lithium ions. Examples of the metal compound particles include oxides such as FeO, Fe2O3, Fe3O4, MnO, MnO2, Mn2O3, Mn3O4, CoO, Co3O4, NiO, Ni2O3, TiO, TiO2, TiO2(B), TiNb2O7, Nb2O5, CuO, NiO, SnO, SnO2, SiO2, RuO2, WO, WO2, WO3, MoO3, and ZnO, metals such as Sn, Si, Al, and Zn, LiVO2, Li3VO4, and Li4Ti5O. 12 , Sc2TiO5, Fe2TiO5, Li2Na2Ti6O 14 , Li2BaTi6O 14 , Li2SrTi6O 14 Complex oxides such as Li 2.6 Co 0.4 Nitrides such as N, Ge3N4, Zn3N2, and Cu3N, as well as Y2Ti2O5S2 and MoS2.
[0027] Among these metal compound particles, oxides or oxyacid salts containing lithium will be specifically described. Oxides or oxyacid salts containing lithium are expressed as LiαMβYγ. In the case of metal oxides, for example, M=Co, Ni, Mn, Ti, Si, Sn, Al, Zn, Mg, Nb, or V, and Y=O. In the case of metal oxyacid salts, for example, M=Fe, Mn, V, Co, or Ni, and Y=PO4, SiO4, BO3, or P2O7. Mβ may be an alloy of MδM'ε, for example, M=Sn, Sb, or Si, and M'=Fe, Co, Mn, V, Ti, or Ni. For example, lithium iron phosphate, lithium titanate, lithium cobalt oxide, lithium vanadium phosphate, and lithium iron manganese phosphate can be used. Among them, lithium titanate (Li4Ti5O 12 ) is preferred.
[0028] The porosity in the cross section of the three-dimensional network structure is preferably in the range of 7 to 50%. If the porosity is less than 7%, the area in contact with the electrolyte is small, which affects the movement of ions in the electrolyte. If the porosity is more than 50%, the bonds between the primary particles 1 become coarse, making it difficult to form a three-dimensional network structure.
[0029] The average particle diameter of the primary particles 1 is in the range of 5 to 300 nm. The average particle diameter is calculated as follows. First, the primary particles 1 are observed using a scanning electron microscope, and an image containing at least 150 or more primary particles 1 is taken. The major and minor axes of the elliptical images of the primary particles 1 contained in one captured field of view (image) are measured, and the average value of the major and minor axes is calculated for each primary particle 1. The average values of each primary particle 1 are then added together, and the sum is divided by the number of primary particles 1 measured. The result falls within the range of 5 to 300 nm.
[0030] When 5 to 300 primary particles 1 are bonded to form a three-dimensional network structure, the metal compound particles acquire many nano-sized pores. This increases the area of the metal compound particles in contact with the electrolyte, facilitating the movement of ions in the electrolyte. In addition, when the pores of the metal compound particles were measured, many fine pores were found. In particular, many fine pores of 40 nm or less were included.
[0031] For metal compound particles having a three-dimensional network structure, the differential pore volume was calculated from the pore distribution measured by nitrogen gas adsorption measurement. As a result, the differential pore volume in the pore diameter range of 10 to 40 nm was 0.01 cm 3 / g or more, especially 0.02 cm 3 Therefore, the area in contact with the electrolyte increases, and the larger the area in contact with the electrolyte, the more improved the discharge rate characteristics are when used in a negative electrode.
[0032] (Coat layer) The coating layer C is formed on a part of the metal compound particle group A. In particular, it is preferable that the coating layer C is formed on at least a part of the surface of the metal compound particle. The coating layer C is a layer containing silicon oxide. The coating layer C may be formed on the surface of the metal compound particle that defines the voids 2 of the metal compound particle group A. That is, the coating layer C may be formed on the surface of the metal compound particle in the voids 2 in the internal structure of the metal compound particle group A as well as on the outer peripheral surface side of the metal compound particle group A. However, the coating layer C is not formed so as to completely fill the voids 2, and the voids 2 remain in the metal compound particle group A on which the coating layer C is formed. Such a metal compound particle group A has a pore size of 0.008 dV for a pore size of 10 nm or less. p / dr p The metal compound particle group A having the coating layer C containing a silicon oxide formed thereon has a reduction rate of integrated strength of 25% or more compared to the metal compound particle group having no coating layer C containing a silicon oxide formed thereon.
[0033] Such a coating layer C is preferably formed so that the content of the Si element in the metal compound particle group A is 0.4 to 3.0 wt%, and within this range, the increase rate of the internal resistance after charging and discharging can be suitably suppressed. If it exceeds 3.0 wt%, the coating layer is excessive for suppressing the generation of deposits, and further suppression effect of the increase rate of the internal resistance cannot be expected, while the influence of the coating layer becomes large and the initial internal resistance increases. More preferably, the coating layer C is preferably formed so that the content of the Si element in the metal compound particle group A is 0.4 to 1.4 wt%, and within this range, the coating layer C is formed on the metal compound particle group A in a well-balanced manner, and the initial internal resistance value is also suppressed.
[0034] The silicon oxide contained in the coating layer C has low crystallinity. That is, the silicon oxide is amorphous and does not have a complete crystal structure. Such amorphous silicon oxide is considered to have good bonding with the metal compound particles. Therefore, the coating layer C containing amorphous silicon oxide is not formed locally on the surface of the metal compound particles. That is, it is formed uniformly on the surface of the metal compound particles and clings to the metal compound particles. Although the bonding state between the silicon oxide and the metal compound particles has not been analyzed, it is considered that the bonding is probably due to physical adsorption such as hydrogen adsorption between the surface functional group of the metal compound particles and the silicon oxide, or chemical bonding between the surface functional group of the metal compound particles and the surface functional group of the silicon oxide.
[0035] In addition, the coating layer C contains about 1% or less of carbon in addition to silicon oxide. Therefore, the coating layer C does not contain any carbon compound or SiOC n H 2n+1 It is believed to contain components such as silicon carbide and silicon carbide.
[0036] The metal compound particle group A as described above is used as an electrode material for an electricity storage device such as a hybrid capacitor or a lithium ion secondary battery. The configuration of a hybrid capacitor using the metal compound particle group A of this embodiment will be described below as an example.
[0037] (1-1. Energy storage devices) A lithium ion secondary battery is an example of an electricity storage device. In a lithium ion secondary battery, a positive electrode and a negative electrode are opposed to each other via a separator to form an element, and the element is impregnated with an electrolyte. A lithium ion secondary battery charges and discharges according to the direction of absorption and release of lithium ions in the positive and negative electrodes. The positive and negative electrodes are each formed by integrating a layer of active material with a current collector. The positive electrode active material and current collector, and the negative electrode active material and current collector are each bonded via a binder using pressure bonding or a doctor blade method, etc.
[0038] The current collector is typically made of a conductive material such as aluminum, copper, iron, nickel, titanium, steel, or carbon. In particular, aluminum or copper, which has high thermal conductivity and electronic conductivity, is preferred. The shape of the current collector may be any shape, such as a film, foil, plate, net, expanded metal, or cylinder.
[0039] Examples of the binder include rubbers such as fluorine-based rubber, diene-based rubber, and styrene-based rubber, fluorine-containing polymers such as polytetrafluoroethylene and polyvinylidene fluoride, celluloses such as carboxymethyl cellulose and nitrocellulose, and also polyolefin resins, polyimide resins, acrylic resins, nitrile resins, polyester resins, phenolic resins, polyvinyl acetate resins, polyvinyl alcohol resins, and epoxy resins. These binders may be used alone or in combination of two or more.
[0040] (1-2. Positive electrode) The positive electrode active material layer is formed by kneading LMO particles, carbon as a conductive assistant, and a binder, and is combined with a current collector. Any carbon can be used as long as it has conductivity, and examples of the carbon include carbon black such as ketjen black, acetylene black, and channel black, fullerene, carbon nanotube, carbon nanofiber, amorphous carbon, carbon fiber, natural graphite, artificial graphite, graphitized ketjen black, mesoporous carbon, and vapor-phase carbon fiber. As the binder, known binders such as polytetrafluoroethylene, polyvinylidene fluoride (PVDF), tetrafluoroethylene-hexafluoropropylene copolymer, polyvinyl fluoride, and carboxymethyl cellulose are used. The content of the binder is preferably 1 to 30 mass% based on the total amount of the electrode material.
[0041] Other positive electrode active materials may be added to this positive electrode active material layer. Examples of other positive electrode active materials include layered rock salt type LiMO2, layered Li2MnO3-LiMO2 solid solution, and spinel type LiM2O4 (wherein M means Fe, Co, Ni, a combination of these, or a combination of these with Mn). Specific examples of these include LiCoO2, LiNiO2, LiNi 4 / 5 Co 1 / 5 O2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 1 / 2 Mn 1 / 2 O2, LiFeO2, LiMnO2, Li2MnO3-LiCoO2, Li2MnO3-LiNiO2, Li2MnO3-LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, Li2MnO3-LiNi 1 / 2 Mn 1 / 2 O2, Li2MnO3-LiNi 1 / 2 Mn 1 / 2 O2-LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiMn 3 / 2 Ni 1 / 2 O4 is an example.
[0042] Other positive electrode active materials besides those mentioned above include sulfur, Li2S, TiS2, MoS2, FeS2, VS2, and Cr. 1 / 2 V 1 / 2 Sulfides such as S2, selenides such as NbSe3, VSe2, NbSe3, Cr2O5, Cr3O8, VO2, V3O8, V2O5, V6O 13 In addition to oxides such as LiNi 0.8 Co 0.15 Al 0.05 O2, LiVOPO4, LiV3O5, LiV3O8, MoV2O8, Li2FeSiO4, Li2MnSiO4, LiFePO4, LiFe 1 / 2 Mn 1 / 2 Examples include complex oxides such as PO4, LiMnPO4, and Li3V2(PO4)3.
[0043] (1-3.Negative electrode) The negative electrode active material is the above-mentioned metal compound particle group A, which is a metal compound particle group capable of absorbing and releasing lithium ions. For example, lithium titanate has an energy storage function by inserting and extracting lithium ions. The volume change due to the insertion and extraction is about 1%, so there is little capacity deterioration. Since the charge / discharge potential is about 1.55V (vs. Li / Li+), side reactions such as decomposition of the electrolyte and precipitation of lithium metal due to rapid charge / discharge are unlikely to occur, and the cycle characteristics are excellent.
[0044] (1-4. Separator) The separator substrate may be made of cellulose such as kraft, Manila hemp, esparto, hemp, or rayon, or a mixture of these materials; polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and derivatives thereof; polytetrafluoroethylene-based resins, polyvinylidene fluoride-based resins, vinylon-based resins, polyamide-based resins such as aliphatic polyamides, semi-aromatic polyamides, and fully aromatic polyamides; polyimide-based resins, polyethylene resins, polypropylene resins, trimethylpentene resins, polyphenylene sulfide resins, and acrylic resins, which may be used alone or in combination.
[0045] (1-5. Electrolyte) The electrolyte of the electrolytic solution is a lithium salt that serves as a lithium ion source. The lithium salt is LiPF6, LiBF4, LiClO4, LiN(SO2CF3)2, LiN(SO2C2F5)2, CF3SO3Li, LiC(SO2CF3)3, and LiPF3(C2F5)3, or a mixture thereof. The concentration of the lithium salt is generally in the range of 0.1 to 2.5 mol / L, preferably 0.5 to 2 mol / L.
[0046] As the electrolyte, a quaternary ammonium salt may be added in addition to the lithium salt. The quaternary ammonium salt is added at a molar concentration of, for example, 1M, although there is no particular limitation, while the lithium salt is added at a molar concentration of 1.6M or more. Examples of the quaternary ammonium salt include tetraethylammonium, triethylmethylammonium, diethyldimethylammonium, ethyltrimethylammonium, methylethylpyrrolidinium, spirobipyrrolidinium, spiro-(N,N')-bipyrrolidinium, 1-ethyl-3-methylimidazolium, and 1-ethyl-2,3-dimethylimidazolium as cations, and BF4 - , PF6 - , ClO4 - , AsF6 - , SbF6 - , AlCl4 - , or RfSO3 - , (RfSO2)2N - , RfCO2 - (Rf is a fluoroalkyl group having 1 to 8 carbon atoms).
[0047] The following solvents are used for the electrolyte. These solvents may be used alone or in combination of two or more. For example, cyclic carbonate esters, chain carbonate esters, phosphate esters, cyclic ethers, chain ethers, lactone compounds, chain esters, nitrile compounds, amide compounds, sulfone compounds, etc. Examples of cyclic carbonate esters include ethylene carbonate, propylene carbonate, butylene carbonate, 4-fluoro-1,3-dioxolan-2-one, 4-(trifluoromethyl)-1,3-dioxolan-2-one, etc., and preferably ethylene carbonate or propylene carbonate.
[0048] Examples of the chain carbonate ester include dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl n-propyl carbonate, methyl isopropyl carbonate, n-butyl methyl carbonate, diethyl carbonate, ethyl n-propyl carbonate, ethyl isopropyl carbonate, n-butyl ethyl carbonate, di-n-propyl carbonate, diisopropyl carbonate, di-n-butyl carbonate, fluoroethyl methyl carbonate, difluoroethyl methyl carbonate, trifluoroethyl methyl carbonate, and the like, and preferred are dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate.
[0049] Examples of the phosphate ester include trimethyl phosphate, triethyl phosphate, ethyl dimethyl phosphate, and diethyl methyl phosphate. Examples of the cyclic ether include tetrahydrofuran and 2-methyltetrahydrofuran. Examples of the chain ether include dimethoxyethane. Examples of the lactone compound include γ-valerolactone and γ-butyrolactone. Examples of the chain ester include methyl propionate, methyl acetate, ethyl acetate, and methyl formate. Examples of the nitrile compound include acetonitrile. Examples of the amide compound include dimethylformamide. Examples of the sulfone compound include sulfolane, methyl sulfolane, dimethyl sulfone, ethyl methyl sulfone, and isopropyl sulfone, but are not limited thereto.
[0050] [2. Manufacturing method] The method for producing a metal compound particle group according to the present invention comprises the following steps. (1) A mixing process in which the base metal compound particles are mixed with the silicon oxide raw material. (2) A heating step in which the powder obtained by the mixing step is heated at 300 to 600°C.
[0051] The metal compound particle group A of this embodiment is produced based on the base metal compound particle group. The base metal compound particle group has a three-dimensional mesh structure. However, no coating layer is formed on the surface of the metal compound particle group. The metal compound particle group is used to carry out the treatments described in the above steps (1) and (2), thereby producing the metal compound particle group A of this embodiment. Each step will be described in detail below.
[0052] (1)Mixing process In the mixing step, the base metal compound particle group and the silicon oxide raw material are mixed to prepare a mixed solution. As the silicon oxide raw material, a silane coupling agent containing silicon atoms can be used. Specifically, a solvent is added to the mixture of the base metal compound particle group and the silane coupling agent to prepare a mixed solution.
[0053] The silane coupling agent is preferably mixed at a ratio of 1 to 20 wt% relative to the weight of the base metal compound particle group, and more preferably at a ratio of 3 to 20 wt%. If the amount of the silane coupling agent mixed is less than 1 wt%, in the electricity storage device made using the metal compound particle group A, deposits are significantly generated on the negative electrode material. Therefore, the effect of suppressing the internal resistance cannot be obtained. In addition, if the amount of the silane coupling agent mixed exceeds 20 wt%, in the electricity storage device made using the metal compound particle group A, the thickness of the coating layer C formed increases.
[0054] Therefore, if the amount of the silane coupling agent is 3 to 20 wt%, the coating layer C in which the amount of Si element contained in the metal compound particle group A is 0.4 to 3.0 wt% is formed by the heating step, and the increase rate of the internal resistance after charging and discharging can be suitably suppressed. Also, if the amount of the silane coupling agent is 3 to 10 wt%, the coating layer C in which the amount of Si element contained in the metal compound particle group A is 0.4 to 1.4 wt% is formed by the heating step, and the thickness of the coating layer C becomes appropriate, and the increase rate of the internal resistance after charging and discharging can be suitably suppressed, and the increase in the initial internal resistance of the electricity storage device can be suppressed.
[0055] The silane coupling agent is not particularly limited, but a typical example is a silane coupling agent made of a compound represented by the general formula below or a salt thereof. [ka] (wherein X1 represents an atomic group having a vinyl group, an amino group, an epoxy group, a chloro group, a mercapto group, a ketimine group, an acryloyl group, a methacryloyl group, a styryl group, a phenyl group, an isocyanate group, an alkyl group, or an alkoxy group; and X2 to X4 represent an alkyl group, an alkoxy group, a chloro group, or a hydroxyl group.) Examples of these silane coupling agents include tetraethoxysilane, vinyltrimethoxysilane, N-(2-aminoethyl)3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, N-[2-(vinylbenzylamino)ethyl]-3-aminopropyltrimethoxysilane hydrochloride, and the like.
[0056] The solvent is not particularly limited as long as it does not adversely affect the reaction, and suitable solvents include water, methanol, ethanol, isopropyl alcohol, etc. Two or more solvents may be mixed and used.
[0057] The mixed solution is thoroughly stirred using a homogenizer or the like so that the metal compound particles and the silane coupling agent are dispersed in the mixed solution. This stirring causes the silane coupling agent to adhere to the surfaces and voids of the base metal compound particles. The mixed solution after stirring is left to stand, and the metal compound particles and the silane coupling agent dispersed in the mixed solution are coagulated, and a mixed powder of the metal compound particles and the silane coupling agent is collected.
[0058] Here, an alkali compound may be further added to the mixed solution. By adding an alkali compound, the amount of silicon oxide attached to the amount of silicon oxide raw material added in the manufacturing process increases, and the increase rate of internal resistance after charging and discharging can be more suitably suppressed with a small amount of silane coupling agent added. Alternatively, when trying to obtain the same suppression effect as when no alkali compound is added, the amount of silicon oxide raw material added in the manufacturing process can be reduced, leading to cost reduction. Although this is a supposition and not limited thereto, it is considered that the catalytic action of the alkali compound improves the reactivity of the metal compound particle group and the silane coupling agent, making it easier for silicon oxide to be attached to the surface of the metal compound particle group. Therefore, it is considered that the amount of silicon oxide attached to the amount of silicon oxide raw material added in the manufacturing process increases, and the increase rate of internal resistance after charging and discharging is suppressed compared to when no alkali compound is added. The amount of the alkali compound added is preferably in the range of 0.05 to 5 mmol per 10 g of metal compound particle group.
[0059] Examples of the alkaline compounds that can be added to the mixed solution include hydroxides, acetates, sulfates, carbonates, nitrates, and chlorides of alkali metals or alkaline earth metals, inorganic alkaline agents, and organic alkaline agents. Examples of the alkali metals and alkaline earth metals include lithium, sodium, potassium, and calcium. Examples of the inorganic alkaline agents include aqueous ammonia. Examples of the organic alkaline agents include amines such as triethylamine, diethylamine, pyridine, and tetramethylguanidine. One or more of these alkaline compounds may be added to the mixed solution.
[0060] In addition, the alkaline compound that is preferably added is, such as a lithium salt, of the same type as the raw material of the metal compound particle group or the electrolyte in the electrolytic solution, and is not an impurity in the characteristics of the metal compound particle group, or is removed by heat treatment or the like during the manufacturing process and does not remain in the metal compound particle group.
[0061] In addition to the method of further adding an alkali compound to the mixed solution, the metal compound particles may be pretreated with an alkali compound before moving to a mixing step with a silane coupling agent. In the pretreatment step, the alkali compound and the metal compound particles are mixed with a solvent, filtered and dried. Then, the filtered and dried mixture is used to proceed to the mixing step. After mixing, the mixture may be left in the range of 30 to 100°C for 1 to 100 hours. If the metal compound particles are pretreated with an alkali compound as in this method, the increase rate of the internal resistance after charging and discharging can be further suitably suppressed. The solvent and alkali compound in this method can be the same as those in the method of further adding an alkali compound to the mixed solution.
[0062] (2)Heating process In the heating step, the mixed powder obtained in the mixing step is subjected to a heat treatment. The heat treatment is preferably performed in a temperature range of 300 to 600°C for 1 to 24 hours. In this heating step, silicon oxide derived from the silane coupling agent is generated in an amorphous state and is believed to bond with the base metal compound particle group.
[0063] Before the heating step, the aggregate obtained in the mixing step may be collected and dried. The drying is preferably performed by heating the aggregate to 20 to 180°C. The heating time is preferably 6 to 48 hours. This drying step provides a mixed powder in which the base metal compound particles and the silane coupling agent are mixed together, with the solvent contained in the aggregate evaporated by heating.
[0064] [3. Effects] The metal compound particle group A of this embodiment and the electricity storage device electrode containing the same have the following effects. (1) A metal compound particle group having a three-dimensional network structure in which metal compound particles are linked together, and a coating layer containing silicon oxide is formed on a part of the metal compound particle group.
[0065] When the metal compound particle group A is used as a negative electrode active material of an electrode for an electricity storage device, the coating layer C prevents deposition from occurring on the negative electrode, thereby making it possible to suppress an increase in the internal resistance of the electricity storage device.
[0066] (2) The coating layer C containing silicon oxide is formed on at least a part of the surface of the metal compound particle.
[0067] The coating layer C formed on the surface of the metal compound particles more reliably prevents deposition from occurring on the surface of the negative electrode, thereby making it possible to suppress an increase in the internal resistance of the electricity storage device.
[0068] (3) The amount of Si element contained based on silicon oxide is 0.4 to 3.0 wt % based on the total weight of the metal compound particle group A.
[0069] By forming the coating layer C so that the amount of Si element contained based on silicon oxide is 0.4 to 3.0 wt% relative to the entire metal compound particle group A, the coating layer C can be given an appropriate thickness and the rate of increase in the internal resistance of the electricity storage device after charging and discharging can be suppressed.
[0070] (4) The amount of silicon element contained based on silicon oxide is 0.4 to 1.7 wt % based on the total weight of the metal compound particles.
[0071] By forming the coating layer C so that the amount of Si element contained based on silicon oxide is 0.4 to 1.7 wt% relative to the entire metal compound particle group A, the coating layer C can be given a more appropriate thickness, and the rate of increase in the internal resistance of the electricity storage device after charging and discharging can be suppressed, as well as the increase in the initial internal resistance of the electricity storage device can be suppressed.
[0072] (5) The three-dimensional network structure has voids 2, and the metal compound particles that define the voids 2 have a coating layer C containing silicon oxide formed on their surfaces.
[0073] The coating layer C is formed on the surface of the metal compound particle A not only on the outer peripheral surface of the metal compound particle A but also in the voids 2 in the internal structure of the metal compound particle group A. By forming the coating layer C sufficiently to reach the voids, it is possible to enhance the effects of suppressing the generation of deposits and the increase in internal resistance.
[0074] (6) The silicon oxide contained in the coating layer C is an amorphous silicon oxide.
[0075] The inclusion of amorphous silicon oxide in the coating layer C improves the bonding between the coating layer C and the metal compound particles. As a result, the metal compound particle group A is obtained in which the coating layer C is bonded uniformly and clings to the metal compound particles. When such metal compound particle group A is used in an electricity storage device, the coating layer C is not dissolved by an electrolyte solution or the like. Therefore, the generation of deposits and an increase in internal resistance can be reliably suppressed in the electricity storage device.
[0076] (7) The pore volume change rate calculated from the pore distribution measured by nitrogen gas adsorption measurement of metal compound particle groups is 0.008 dV for pore diameters of 10 nm or less. p / dr p The pore volume change rate is greater than 1.0.
[0077] 0.008dV for pore sizes below 10nm p / dr p In the metal compound particle group having a pore volume change rate of 0.01 or more, clogging of the pores is eliminated. In other words, the coating layer C is not formed so as to fill the pores. Therefore, it is possible to suppress an increase in the initial internal resistance.
[0078] (8) The reduction rate of integrated intensity is 25% or more compared to a group of metal compound particles on which a coating layer containing silicon oxide is not formed.
[0079] The integral intensity ratio is lower in the metal compound particle group having the coating layer C formed thereon than in the metal compound particle group not covered with the coating layer containing silicon oxide. In the metal compound particle group of this embodiment, the coating layer C suppresses the generation of deposits on the negative electrode, so that an increase in internal resistance can be suppressed.
[0080] In addition, the power storage device can provide the following advantageous effects. (9) An element having a negative electrode constituted by containing the metal compound particle group A and a positive electrode, and an electrolyte impregnated in the element, the electrolyte containing a fluorine-containing compound.
[0081] In an electricity storage device, for example, when a fluorine-containing compound such as LiPF6 or LiBF4 is used in the electrolyte, it is considered that the components in the electrolyte react on the surface of the negative electrode, and fluorine-derived deposits are generated on the negative electrode. It is speculated that the metal compound particle group A of the present embodiment is particularly effective in suppressing the generation of these fluorine-derived deposits.
[0082] In addition, the method for producing metal compound particle groups can provide the following effects. (10) The method includes a mixing step of mixing the base metal compound particles with a silicon oxide raw material, and a heating step of heating the powder obtained in the mixing step at 300 to 600°C.
[0083] A coating layer C containing silicon oxide derived from the silicon oxide raw material is formed on the surface of the metal compound particles by subjecting a mixed powder of the base metal compound particle group and the silicon oxide raw material to a heat treatment at 300 to 600° C. This heat treatment causes the silicon oxide to become amorphous, improving the bond with the metal compound particles.
[0084] (11) The silicon oxide raw material is mixed in a ratio of 1 to 20 wt % based on the weight of the base metal compound particle group.
[0085] By mixing 1 to 20 wt % of silicon oxide raw material, a suitable amount of coating layer C is formed on the metal compound particles. That is, it is possible to form a coating layer C that can suppress an increase in the initial internal resistance while suppressing an increase in the internal resistance after charging and discharging.
[0086] (12) The silicon oxide raw material is mixed in a ratio of 3 to 20 wt % based on the weight of the base metal compound particle group.
[0087] By mixing 3 to 20 wt% of silicon oxide raw material, a coating layer C of an appropriate thickness is formed by heat treatment at 300 to 600°C, in which the amount of Si element contained in the metal compound particle group A is 0.4 to 3.0 wt%, and the rate of increase in internal resistance after charge and discharge can be suitably suppressed.
[0088] (13) The silicon oxide raw material is mixed in a ratio of 3 to 10 wt % based on the weight of the base metal compound particle group.
[0089] By mixing 3 to 10 wt% of silicon oxide raw material, a coating layer C of an appropriate thickness is formed by heat treatment at 300 to 600°C, in which the amount of Si element contained in the metal compound particle group A is 0.4 to 1.7 wt%. This makes it possible to suitably suppress the rate of increase in internal resistance after charging and discharging, and also suppresses an increase in the initial internal resistance of the energy storage device.
[0090] (14) In the mixing step, one or more kinds of alkaline compounds are further mixed in. Examples of the alkaline compounds include hydroxides, acetates, sulfates, carbonates, nitrates, chlorides, inorganic alkaline agents, and organic alkaline agents of alkali metals or alkaline earth metals.
[0091] If these alkaline compounds are added in the mixing step, the amount of silicon oxide attached to the amount of silicon oxide raw material added in the manufacturing process increases, and the increase rate of internal resistance after charging and discharging can be more suitably suppressed with a small amount of silane coupling agent added. Alternatively, when trying to obtain the same suppression effect as when no alkaline compounds are added, the amount of silicon oxide raw material added in the manufacturing process can be reduced, leading to cost reduction.
[0092] (15) Alternatively, prior to the mixing step, the base metal compound particles are pretreated with an alkali compound.
[0093] If the metal compound particles are pretreated with an alkali compound, the rate of increase in internal resistance after charge and discharge can be further suitably suppressed. EXAMPLES
[0094] The present invention will be described with reference to the following examples, but the present invention is not limited to the following examples.
[0095] Example 1 In Example 1, lithium titanate was used as the base metal compound particle group, and (CH3O)3SiC3H6OCOCH=CH2 containing an acryloyl group as an organic functional group was used as the silane coupling agent. The silane coupling agent was mixed at 5 wt% with respect to the lithium titanate. In the mixing process, a homogenizer was used to stir at a rotation speed of 15,000 for 10 minutes. The aggregates were collected after standing and vacuum dried at 150°C for 12 hours. The dried powder was then heat-treated at 400°C for 3 hours.
[0096] Example 2 In Example 2, the silane coupling agent was mixed in an amount of 10 wt % relative to the lithium titanate, but the rest of the process was the same as in Example 1.
[0097] Example 3 In Example 3, the silane coupling agent was mixed in an amount of 20 wt % with respect to the lithium titanate, but the rest of the process was the same as in Example 1.
[0098] Example 4 In Example 4, the silane coupling agent was mixed in an amount of 3 wt % with respect to the lithium titanate, but the rest of the process was the same as in Example 1.
[0099] Example 5 In Example 5, 3-glycidoxypropyltrimethoxysilane containing an epoxy group as an organic functional group was used as a silane coupling agent, and was mixed with lithium titanate at 3 wt%. Other than that, the preparation was the same as in Example 1. That is, the difference from Example 4 is that the silane coupling agent is an epoxy type.
[0100] Example 6 In Example 6, 3-glycidoxypropyltrimethoxysilane was used as a silane coupling agent and mixed with lithium titanate at 5 wt%. Other than that, the sample was produced in the same manner as in Example 1. That is, the silane coupling agent was epoxy-based like in Example 5, but the amount of the silane coupling agent added was different from that in Example 5.
[0101] Example 7 In Example 7, 3-glycidoxypropyltrimethoxysilane was used as a silane coupling agent and mixed with lithium titanate at 10 wt%. Other than that, the sample was produced in the same manner as in Example 1. That is, the silane coupling agent was an epoxy-based agent as in Example 5, but the amount of the silane coupling agent added was different from that in Example 5.
[0102] Example 8 In Example 8, 3-glycidoxypropyltrimethoxysilane was used as a silane coupling agent and mixed with lithium titanate at 20 wt%. Other than that, the sample was produced in the same manner as in Example 1. That is, the silane coupling agent was an epoxy-based agent as in Example 5, but the amount of the silane coupling agent added was different from that in Example 5.
[0103] Example 9 In Example 9, 3-glycidoxypropyltrimethoxysilane was used as a silane coupling agent and mixed with lithium titanate at 3 wt%. In Example 9, lithium hydroxide was added as an alkaline compound in addition to lithium titanate and the silane coupling agent, and a mixing process was performed. Lithium hydroxide was added at a ratio of 0.25 mmol per 10 g of lithium titanate. Other than that, the preparation was the same as in Example 1. That is, it differs from Example 5 in that an alkaline compound was added.
[0104] Example 10 In Example 10, 3-glycidoxypropyltrimethoxysilane was used as a silane coupling agent and mixed with lithium titanate at 5 wt%. Otherwise, the sample was prepared in the same manner as in Example 9. That is, an alkaline compound was added in the same manner as in Example 9, but the amount of the silane coupling agent added was different from that in Example 9.
[0105] Example 11 In Example 11, 3-glycidoxypropyltrimethoxysilane was used as a silane coupling agent and mixed with lithium titanate at 10 wt%. Other than that, the sample was prepared in the same manner as in Example 9. That is, an alkaline compound was added in the same manner as in Example 9, but the amount of the silane coupling agent added was different from that in Example 9.
[0106] Example 12 In Example 12, 3-glycidoxypropyltrimethoxysilane was used as a silane coupling agent and mixed with lithium titanate at 20 wt%. Other than that, the sample was prepared in the same manner as in Example 9. That is, an alkaline compound was added in the same manner as in Example 9, but the amount of the silane coupling agent added was different from that in Example 9.
[0107] Example 13 In Example 13, 3-glycidoxypropyltrimethoxysilane was used as a silane coupling agent and mixed with lithium titanate at 3 wt%. However, before the mixing step of adding the silane coupling agent, lithium hydroxide, which is an alkaline compound, water, which is a solvent, and lithium titanate, which is a base metal compound particle group, were mixed, stirred with a stirrer for 30 minutes, left at 60°C for 64 hours, filtered, washed with water, and dried at 30°C for 24 hours for pretreatment. Lithium hydroxide was added at a ratio of 2.5 mmol per 10 g of lithium titanate. Other than that, it was prepared in the same manner as in Example 9. That is, it is different from Example 9 in that the base metal compound particle group is pretreated with an alkaline compound.
[0108] Comparative Example 1 In Comparative Example 1, the same treatment as in Example 1 was carried out on lithium titanate without mixing a silane coupling agent.
[0109] Comparative Example 2 In Comparative Example 2, no silane coupling agent was mixed in. After the mixing step, only vacuum drying was performed, and no heat treatment was performed.
[0110] Comparative Example 3 In Comparative Example 3, the silane coupling agent was mixed in an amount of 5 wt % with respect to the lithium titanate. After the mixing process, only vacuum drying was performed, and no heat treatment was performed.
[0111] Comparative Example 4 In Comparative Example 4, the silane coupling agent was mixed in an amount of 10 wt % with respect to the lithium titanate. After the mixing process, only vacuum drying was performed, and no heat treatment was performed.
[0112] Comparative Example 5 In Comparative Example 5, the silane coupling agent was mixed in an amount of 20 wt % with respect to the lithium titanate. After the mixing process, only vacuum drying was performed, and no heat treatment was performed.
[0113] Comparative Example 6 In Comparative Example 6, the silane coupling agent was mixed in an amount of 3 wt % with respect to the lithium titanate. After the mixing process, only vacuum drying was performed, and no heat treatment was performed.
[0114] (About the formation of the coating layer) First, the results of observing the obtained lithium titanate particle groups will be described below. Figures 2 to 4 are SEM images of the lithium titanate particle groups of Comparative Example 1, Comparative Example 4, and Example 2 taken by a scanning electron microscope.
[0115] 2 is an SEM image (×50.0K) of the lithium titanate particles of Comparative Example 1. The lithium titanate particles of Comparative Example 1 to which no silane coupling agent is added have a three-dimensional network structure. However, the coating layer C is not formed on the outer peripheral surface and void surface of the lithium titanate particles.
[0116] FIG. 3 is an SEM image of the lithium titanate particle group of Comparative Example 4 and Example 2. FIG. 3(a) is an SEM image of the lithium titanate particle group of Comparative Example 4, with the upper magnification of ×50.0K and the lower magnification of ×100K. As is clear from FIG. 3(a), in Comparative Example 4, in which 10 wt% of the silane coupling agent was mixed and only drying was performed, the outer surface and the surface of the voids of the lithium titanate particle group are in a state of being covered with the silane coupling agent. The silane coupling agent is attached to the lithium titanate particle group so as to fill the voids of the lithium titanate particle group.
[0117] On the other hand, Fig. 3(b) is an SEM image of the lithium titanate particle group of Example 2, the upper part is ×50.0K, and the lower part is ×100K. As is clear from Fig. 3(b), in Example 2 in which 10wt% of the silane coupling agent was mixed and then dried and heated, a coating layer containing silicon oxide derived from the silane coupling agent was formed on the outer peripheral surface and the surface of the voids of the lithium titanate particle group. The coating layer was formed on the surface of the lithium titanate particles even in the voids of the lithium titanate particle group, but was not formed so as to fill the voids.
[0118] Here, the results of elemental analysis of the lithium titanate particle groups of Comparative Example 4 and Example 2 are shown in FIG. 4. FIG. 4(a) shows the analysis results of the lithium titanate particle group of Comparative Example 4, and FIG. 4(b) shows the analysis results of the lithium titanate particle group of Example 2. The elemental analysis was performed across the diameter of the lithium titanate particle group, as shown by the arrows in the SEM images in each figure. In the graphs in the figures, the vertical axis is plotted as the Si / Ti ratio, and the proportion of Si derived from the silane coupling agent is verified.
[0119] 4(a) and (b) show that Si is present not only on the outer surface of the lithium titanate particle group in Comparative Example 4 and Example 2, but also on the particle surface in the void portion of the internal structure. That is, it was found that Si is present not locally but overall in both the lithium titanate particle groups in Comparative Example 4 and Example 2.
[0120] (Pore size distribution) Next, the pore size distribution of the obtained lithium titanate particle groups of Examples 1 and 2 and Comparative Examples 2 to 4 was measured. The measurement method used was a nitrogen gas adsorption measurement method. Specifically, nitrogen gas was introduced into the surface of the lithium titanate particles and into pores formed inside the lithium titanate particles and communicating with the surface of the lithium titanate particles, and the amount of adsorbed nitrogen gas was determined. Next, the pressure of the introduced nitrogen gas was gradually increased, and the amount of adsorbed nitrogen gas was plotted against each equilibrium pressure to obtain an adsorption isotherm. The measurement was performed using a high-precision gas / vapor adsorption measurement device BELSORP-max-N (manufactured by BEL Japan Co., Ltd.).
[0121] In Figures 5 and 6, the horizontal axis shows the pore diameter and the vertical axis shows the rate of change in pore volume dV p / d(r p) is plotted. FIG. 5 shows the pore size distribution data of Comparative Examples 2 to 4 in which heating was not performed. As is clear from FIG. 5, the number of voids of 10 nm or less is significantly reduced in Comparative Examples 3 and 4 in which a silane coupling agent is mixed, compared to Comparative Example 2 in which a silane coupling agent is not mixed. In other words, it was found that the voids are filled by the silane coupling agent in Comparative Examples 3 and 4 in which a silane coupling agent is mixed.
[0122] FIG. 6 shows the pore size distribution data of Comparative Example 1, Example 1, and Example 2, which were heated. As is clear from FIG. 6, Examples 1 and 2, in which a silane coupling agent was mixed, have voids of the same degree as Comparative Example 1, in which a silane coupling agent was not mixed. Specifically, in Examples 1 and 2, the pore volume change rate of pores with a diameter of 10 nm or less was 0.008 dV p / dr p It has a value exceeding 0.008. The pore volume change rate does not need to be uniformly more than 0.008 in the pore diameter of 10 nm or less, but it is sufficient if it exceeds 0.008 in some parts. In Examples 1 and 2 in which a silane coupling agent was mixed and heated, it was found that the clogging of the pores was eliminated by forming a coating layer containing silicon oxide derived from the silane coupling agent.
[0123] (Regarding internal resistance) In order to verify the internal resistance, lithium ion secondary batteries were produced using the lithium titanate particles of Examples 1 to 4 and Comparative Examples 1 to 6. Specifically, 5% by weight of polyvinylidene fluoride and an appropriate amount of N-methylpyrrolidone were added to each particle group, and the mixture was thoroughly kneaded to form a slurry, which was then applied to an aluminum foil and dried to obtain a negative electrode. In addition, a slurry-like mixed solution was produced by adding LMO particles, acetylene black as a conductive assistant, and polyvinylidene fluoride (PVDF) as a binder to a solvent and stirring with a homogenizer. This mixed solution was applied to an aluminum current collector foil, dried, and pressed to obtain a sheet of a positive electrode active material layer, which was used as a positive electrode. A cellulose separator was interposed between the positive electrode and the negative electrode to form an element, and the element was impregnated with an electrolyte. The electrolyte used LiBF4 with a 1.6 molar concentration as a solute and γ-butyrolactone (GBL) as a solvent. The element impregnated with the electrolytic solution was then heat sealed using a laminate film to prepare the lithium ion secondary batteries according to Examples 1-4 and Comparative Examples 1-6.
[0124] The initial internal resistance (DCIR) of the lithium ion secondary batteries thus prepared in Examples 1 to 4 and Comparative Examples 1 to 6 was measured, and the results are shown in Fig. 7. In Fig. 7, the series connecting the plots of circles is the series which underwent the heating step and consists of the results of Comparative Example 1 and Examples 1 to 4, while the series connecting the plots of triangles is the series which omitted the heating step and consists of the results of Comparative Examples 2 to 6.
[0125] From FIG. 7, in Comparative Examples 1 and 2 in which the silane coupling agent was not mixed, no change occurred in the initial DCIR. Next, referring to the circle series, comparing Comparative Example 1, which was subjected to heat treatment, with Examples 1 to 4, Example 4, in which the silane coupling agent was mixed at 3 wt%, Example 1, in which the silane coupling agent was mixed at 5 wt%, and Example 2, in which the silane coupling agent was mixed at 10 wt%, the internal resistance increased compared to Comparative Example 1, but the increasing tendency was gradual. On the other hand, when Example 3, in which the silane coupling agent was mixed at 20 wt%, was examined, the internal resistance increased significantly compared to Comparative Example 1. Therefore, it was thought that the internal resistance would increase further if the silane coupling agent was mixed at more than 20 wt%.
[0126] In addition, when the series of triangle marks is referred to and comparative examples 2 to 6 in which heat treatment is not performed are examined, the internal resistance of comparative examples 3 to 6 in which a silane coupling agent is mixed is significantly increased compared to comparative example 2 in which a silane coupling agent is not mixed. When comparing the series of triangle marks with the series of circles, it is found that the increase in internal resistance is suppressed in examples 1 to 4 in which heat treatment is performed at each mixing ratio. This is because the silane coupling agent fills the voids in comparative examples 3 to 6 in which heat treatment is not performed, so the impregnation of the electrolyte is reduced and the initial internal resistance is increased. On the other hand, in examples 1 to 4 in which heat treatment is performed, the coating layer is not formed to fill the voids. Therefore, it is considered that the increase in the initial internal resistance is suppressed. It is presumed that this is probably due to the organic portion of the silane coupling agent being burned off by the heat treatment, resulting in the creation of voids.
[0127] Next, a charge / discharge test was performed at 60°C, with a voltage range of 1.5 to 2.7 V, and a current of 20 mA, and the rate of increase in internal resistance was calculated from the initial internal resistance and the internal resistance after charge / discharge. FIG. 8 shows the rate of increase in internal resistance after 2000 cycles. The rate of increase in internal resistance was calculated from the internal resistance after charge / discharge / initial internal resistance. In FIG. 8, the series connecting the plots of circles is a series that underwent a heating process, and is made up of the results of Comparative Example 1 and Examples 1 to 4, while the series connecting the plots of triangles is a series that omits the heating process, and is made up of the results of Comparative Examples 2 to 6.
[0128] First, in Comparative Examples 1 and 2, the increase rate of the internal resistance was 166.4%. In Comparative Examples 1 and 2, since the silane coupling agent was not mixed, deposits were generated on the negative electrode, and the internal resistance increased significantly. Comparing Comparative Example 1, which was subjected to heat treatment, with Examples 1 to 4 with reference to the circle series, first, in Example 4, in which 3 wt% of the silane coupling agent was mixed, the increase rate was 118.4%, which is suppressed compared to Comparative Example 1. In addition, in Example 1, in which 5 wt% of the silane coupling agent was mixed, the increase rate was 93.3%, which is suppressed compared to Comparative Example 1. In addition, in Example 2, in which 10 wt% of the silane coupling agent was mixed, the increase rate was 61.2%, which increased the suppression effect of the increase rate. Next, in Example 3, in which 20 wt% of the silane coupling agent was mixed, the increase rate was 62.5%, which was slightly higher than Example 2. From this result, it was found that even when 10 wt% or more of the silane coupling agent was mixed, the suppression effect of the increase rate remained flat.
[0129] From the above, it was found that the initial internal resistance increases significantly when the silane coupling agent is mixed in an amount of more than 20 wt%. It was also found that the generation of deposits can be prevented and the increase in internal resistance after charging and discharging can be suppressed when the silane coupling agent is mixed in an amount of 1 wt% or more. In particular, it was made clear that by mixing the amount of silane coupling agent in the range of 3 to 10 wt%, the increase in the initial internal resistance of the power storage device can be suppressed, and the increase rate of the internal resistance after charging and discharging can be suitably suppressed.
[0130] In addition, when the series of triangle marks is referred to and comparative examples 2 to 6, which were not subjected to heat treatment, are examined, the increase rate of the internal resistance is reduced in comparative examples 3 to 6, which contain a silane coupling agent, compared to comparative example 2, which does not contain a silane coupling agent. Therefore, it was confirmed that the effect of suppressing the increase rate can be obtained by adding a silane coupling agent.
[0131] However, when comparing the series of triangles and circles, it was found that, at each mixing ratio, Examples 1 to 4, which were subjected to heat treatment, had a lower increase rate of internal resistance. This was thought to be due to the fact that, in Comparative Examples 3 to 6, which were not subjected to heat treatment, the silane coupling agent did not form a coating layer on the surface of the lithium titanate particle group, and the silane coupling agent simply adhered to the surface of the lithium titanate particle group. Therefore, in Comparative Examples 3 to 6, it was suggested that the silane coupling agent attached to the surface of the lithium titanate particle group was dissolved by the electrolyte, and a deposit was formed on the negative electrode.
[0132] Furthermore, lithium ion secondary batteries were manufactured using the lithium titanate particle group of Examples 5 to 8, which was produced using an epoxy-based silane coupling agent, as the negative electrode active material layer. The manufacturing method and manufacturing conditions for these lithium ion secondary batteries were the same as those for the lithium ion secondary batteries using the lithium titanate particle group of Examples 1 to 4 and Comparative Examples 1 to 6. The initial internal resistance (DCIR) and the increase rate of internal resistance after 2000 cycles were measured for the lithium ion secondary battery using the lithium titanate particle group of Examples 5 to 8, as well as the lithium ion secondary battery using the lithium titanate particle group of Comparative Example 1, to which no silane coupling agent was added. The method for measuring the initial internal resistance and the increase rate of internal resistance was the same as in Examples 1 to 4 and Comparative Example 1.
[0133] The measurement results are shown in Figures 9 and 10. Figure 9 is a graph showing the relationship between the amount of silane coupling agent added and the initial internal resistance (DCIR). Figure 10 is a graph showing the relationship between the amount of silane coupling agent added and the rate of increase in internal resistance. As shown in Figures 9 and 10, it was confirmed that the initial internal resistance (DCIR) and the rate of increase in internal resistance showed the same trends as in Examples 1 to 4, even when the type of silane coupling agent was changed.
[0134] That is, it was confirmed that, regardless of the type of silane coupling agent, if the silane coupling agent is mixed at 1wt% or more, the generation of deposits is prevented. And, it was confirmed that, regardless of the type of silane coupling agent, if the amount of the silane coupling agent added is 20wt% or less, the increase in internal resistance associated with the increase in the silane coupling agent is gradually contained. Furthermore, it was made clear that, by making the amount of the silane coupling agent mixed 3-10wt%, regardless of the type of silane coupling agent, the increase in the initial internal resistance of the power storage device can be suppressed, and the increase rate of the internal resistance after charging and discharging can be suitably suppressed.
[0135] Furthermore, lithium ion secondary batteries were manufactured using the lithium titanate particle groups of Examples 9 to 12, which were prepared while adding a silane coupling agent and lithium hydroxide as an alkaline compound, as the negative electrode active material layer. The manufacturing methods and manufacturing conditions for these lithium ion secondary batteries were the same as those for the lithium ion secondary batteries using the lithium titanate particle groups of Examples 1 to 8 and Comparative Examples 1 to 5. The initial internal resistance (DCIR) and the rate of increase in internal resistance after 2000 cycles were measured for the lithium ion secondary batteries using the lithium titanate particle groups of Examples 9 to 12, as well as the lithium ion secondary battery using the lithium titanate particle groups of Comparative Example 1, to which no silane coupling agent was added. The methods for measuring the initial internal resistance and the rate of increase in internal resistance were the same as those for Examples 1 to 8 and Comparative Example 1.
[0136] The measurement results are shown in Figures 11 and 12. Figure 11 is a graph showing the relationship between the amount of silane coupling agent added and the initial internal resistance (DCIR). Figure 12 is a graph showing the relationship between the amount of silane coupling agent added and the rate of increase in internal resistance. As shown in Figure 11, it was confirmed that the initial internal resistance (DCIR) value did not change or was slightly lowered in the lithium titanate particle group produced with the addition of a silane coupling agent and an alkaline compound compared to the case where no alkaline compound was added. On the other hand, as shown in Figure 12, it was confirmed that the increase rate of internal resistance was further suppressed in the lithium titanate particle group produced with the addition of a silane coupling agent and an alkaline compound compared to the case where no alkaline compound was added.
[0137] For example, comparing FIG. 12 with FIG. 10, when the amount of the silane coupling agent added was 3 wt%, there was a difference of 21.6% in the increase rate of the internal resistance depending on whether or not an alkaline compound was added. When the amount of the silane coupling agent added was 5 wt%, there was a difference of 7.5% in the increase rate of the internal resistance depending on whether or not an alkaline compound was added. When the amount of the silane coupling agent added was 10 wt%, there was a difference of 10.4% in the increase rate of the internal resistance depending on whether or not an alkaline compound was added. When the amount of the silane coupling agent added was 20 wt%, there was a difference of 6.9% in the increase rate of the internal resistance depending on whether or not an alkaline compound was added. In particular, when an alkaline compound was added, the increase rate of the internal resistance when the amount of the silane coupling agent added was 20 wt% was suppressed to the same as when the amount of the silane coupling agent added was 10 wt% without the addition of an alkaline compound.
[0138] That is, it was confirmed that the addition of an alkaline compound during the manufacturing process enhances the effect of suppressing the rate of increase in internal resistance relative to the amount of silane coupling agent added during the manufacturing process.
[0139] Next, lithium hydroxide was used as an alkaline compound, and water and lithium titanate particles were mixed, followed by pretreatment such as filtration and drying. Then, a lithium ion secondary battery was fabricated using the lithium titanate particle group of Example 13, which was produced using a silane coupling agent, as the negative electrode active material layer. The manufacturing method and manufacturing conditions for these lithium ion secondary batteries were the same as those for the lithium ion secondary batteries using the lithium titanate particle group of Examples 1 to 8 and Comparative Examples 1 to 5. Then, the initial internal resistance (DCIR) and the increase rate of the internal resistance after 2000 cycles were measured. The method for measuring the initial internal resistance and the increase rate of the internal resistance were the same as those for Examples 1 to 8 and Comparative Example 1.
[0140] The measurement results are shown in Table 1 below. Table 1 below also shows the results of a lithium ion secondary battery in which the lithium titanate particle group of Example 9 was used as the negative electrode active material layer. Example 13 differs from Example 9 in that the lithium titanate particle group was pretreated with an alkaline compound before moving to the mixing step of the silane coupling agent, whereas Example 9 mixed the lithium titanate particle group, the alkaline compound, and the silane coupling agent. (Table 1) TIFF0007640265000002.tif31101
[0141] As shown in Table 1, there was almost no difference in the initial internal resistance between Examples 9 and 13. However, the internal resistance increase rate after 2000 cycles was even better in Example 13. That is, it was confirmed that the effect of suppressing the increase rate of the internal resistance was further enhanced by pretreating the metal compound particle group with an alkali compound in advance.
[0142] (Si content in comparative examples) In Comparative Examples 3 to 6, the reason why the suppression effect on the rate of increase in internal resistance was low was examined. Specifically, a mixed solvent was prepared by adding lithium titanate particles and a silane coupling agent (10 wt%) to isopropyl alcohol. The mixed solvent was stirred using a homogenizer, and the obtained aggregate was dried at 150°C for 12 hours. No heat treatment was performed. The dried powder was washed three times using isopropyl alcohol. The washed powder was dried at 150°C for 12 hours.
[0143] The results of thermogravimetry of the powder after drying and the powder after washing and drying are shown in FIG. 13(a). As shown in FIG. 13(a), the powder before washing lost 5.24 wt% of its weight due to heating. On the other hand, the powder after washing and drying lost 1.51 wt% of its weight due to heating. When this 1.51 wt% loss is converted to the amount of silane coupling agent, it becomes 1.7 wt% as shown in FIG. 13(b). In other words, it is clear that the silane coupling agent contained in the powder before washing was 10 wt%, but after washing it was reduced to 1.7 wt%. In this way, in Comparative Examples 3 to 6 where no heat treatment was performed, the silane coupling agent was dissolved in the solvent, and therefore, as described above, the effect of suppressing the increase in internal resistance was reduced.
[0144] When the amount of silane coupling agent is 1.7wt% relative to the total amount of lithium titanate particles, the content of Si element contained in the lithium titanate particles is converted to 0.3wt%. Therefore, from the results shown in Figure 13, it can be said that by adding 10wt% of silane coupling agent, lithium titanate particles containing 0.3wt% of Si element were produced without heat treatment.
[0145] (Si content in examples) The amount of Si element remaining in the lithium titanate particle group of Examples 1 to 4 and Comparative Example 1 was measured. The amount of Si element was quantified by an alkali fusion method. That is, the lithium titanate particle group of Examples 1 to 4 and Comparative Example 1 and a flux were placed in a platinum crucible and melted by heating, and an acid was further added to dissolve the lithium titanate particle group of Examples 1 to 4 and Comparative Example 1. The amount of Si was then quantified by ICP-AES (inductively coupled plasma atomic emission spectrometry). The results are shown in FIG. 14. FIG. 14 is a graph showing the relationship between the amount of silane coupling agent added and the amount of Si element contained in the lithium titanate particle group.
[0146] As shown in Fig. 14, when 10wt% of the silane coupling agent was mixed and heat treatment was performed after the mixing process, the amount of Si element remaining in the lithium titanate particle group was 1.36wt%. In Comparative Example 4, in which the same amount of silane coupling agent was mixed but heat treatment was not performed after the mixing process, the amount of Si element remaining in the lithium titanate particle group was 0.3wt% based on the results shown in Fig. 9, so it can be confirmed that the Si content is dramatically increased. In addition, when 3wt% or more of the silane coupling agent was added, it was confirmed that more Si element remained due to heat treatment after the mixing process than in Comparative Example 4.
[0147] And, combining the results shown in Fig. 8 and the results shown in Fig. 14, as in Examples 1 to 4, by adding silane coupling agent at 3wt% to 20wt% and performing heat treatment after the mixing process, lithium titanate particle group with Si element content of 0.4wt% to 3.0wt% can be produced, and it was confirmed that this lithium titanate particle group can suppress the increase in internal resistance well. Furthermore, combining the results shown in Fig. 7 and the results shown in Fig. 14, as in Examples 1, 2 and 4, by adding silane coupling agent at 3wt% to 10wt% and performing heat treatment after the mixing process, lithium titanate particle group with Si element content of 0.4wt% to 1.4wt% can be produced, and it was confirmed that this lithium titanate particle group can suppress the initial internal resistance.
[0148] (Regarding Si in the Examples) Next, in Examples 1 to 4 in which heat treatment was performed, the form of the silane coupling agent on the surface of the lithium titanate particle group was examined. Specifically, in order to confirm the reaction of the silane coupling agent during heat treatment, the silane coupling agent of (CH3O)3SiC3H6OCOCH=CH2 was heated and elemental analysis was performed. Specifically, an aggregate in which the silane coupling agent (10 wt%) was mixed with the lithium titanate particle group was dried at 150°C for 12 hours. After drying, the mixture was subjected to heat treatment from 300°C to 500°C. The powder after the heat treatment was subjected to carbon weight measurement using a carbon analyzer. FIG. 15(a) is a graph showing the carbon concentration (wt%) of the silane coupling agent at each heating temperature. FIG. 15(b) is a graph showing the silicon concentration (wt%) of the silane coupling agent at each heating temperature. Also, FIG. 15(c) is a graph showing the carbon / silicon ratio at each heating temperature.
[0149] As is clear from Figure 15(a), the carbon content of the silane coupling agent decreased as the heating temperature increased. When the heating temperature reached 300°C, the carbon content decreased significantly, and at 400°C it had almost completely disappeared. On the other hand, as is clear from Figure 15(b), the silicon content of the silane coupling agent remained almost constant regardless of the heating temperature.
[0150] As is clear from the graph of the carbon / silicon ratio in Figure 15(c) created based on these results, it was presumed that the carbon in the silane coupling agent disappeared during the heating process, resulting in a composition very close to silicon oxide. In other words, it was thought that by heating the silane coupling agent at 300 to 600°C, it became silicon oxide rather than a silane coupling agent, and a coating layer was formed on the surface of the metal compound particle group.
[0151] Next, X-ray photoelectron spectroscopy was performed on the lithium titanate particles mixed with 10 wt% silane coupling agent. Figure 16 is a graph showing the results of measuring the lithium titanate particles before and after heat treatment. The bond energy of 103 eV indicates that Si-OH and Si-OC are the constituent functional groups. Also, the bond energy of 104 eV indicates that Si-O-Si and SiO2 are the constituent functional groups.
[0152] As is clear from Fig. 16, the spectrum of the lithium titanate particles before the heat treatment has a peak at the midpoint between 103 eV and 104 eV. On the other hand, the peak of the lithium titanate particles after the heat treatment shifts to around 104 eV. That is, it was found that the lithium titanate particles after the heat treatment have a peak very close to that of SiO2, although it is considered that they also contain SiO and Si.
[0153] Next, the results of X-ray diffraction analysis of the lithium titanate particles after the heat treatment are shown in FIG. 17. As shown by the dotted line in the figure, SiO2 has a peak at around 24 degrees. However, no peak indicating SiO2 appeared in the spectrum of the lithium titanate particles after the heat treatment. This is because the SiO2 peak detected at around 24 degrees in the X-ray diffraction analysis is a crystalline silicon oxide. In other words, although a peak very close to SiO2 was confirmed in the X-ray photoelectron spectroscopy analysis, no peak indicating SiO2 was confirmed in the X-ray diffraction analysis, which revealed that the silicon oxide contained in the coating layer was amorphous.
[0154] (solid 1 H-NMR FIG. 18(a) shows the solid state of the lithium titanate particles obtained in Example 2 and Comparative Example 1. 1 The data shown is H-NMR. The measurement was performed using a nuclear magnetic resonance analyzer (JNM-ECA600 manufactured by JEOL Ltd.). The peaks present at 5 to 8 ppm indicate surface hydroxyl groups (bridge OH) of the lithium titanate particle groups.
[0155] The integrated intensity of the peaks present at 5 to 8 ppm in FIG. 18(a) was calculated using waveform separation software, and the result is shown in FIG. 13(b). As is clear from FIG. 18(b), it was found that the integrated intensity of the lithium titanate particle group of Example 2 was reduced by about 44% compared to the integrated intensity of the lithium titanate particle group of Comparative Example 1. In other words, it is shown that the peak of the hydroxyl group (Bridge OH) present on the surface of the lithium titanate particle group of Example 2 is reduced by the attachment of the silicon compound. In other words, it is considered that Example 2 is a form in which about 44% of the surface of the lithium titanate particle group of Comparative Example 1, which is not coated with silicon oxide, is coated with silicon oxide.
[0156] Next, Fig. 19 shows the increase rate of internal resistance after 2000 cycles of lithium ion secondary batteries using the lithium titanate particle groups of Example 1, Example 2, and Comparative Example 1. Example 1, in which the decrease rate of integral strength is 29%, and Example 2, in which the decrease rate of integral strength is 44%, both have a suppressed increase rate of internal resistance after 2000 cycles compared to the lithium ion secondary battery of Comparative Example 1, and thus show good results. This is believed to be because the coating of the surface of the lithium titanate particle group with silicon oxide has suppressed the formation of deposits on the negative electrode. From the viewpoint of suppressing an increase in internal resistance, it is desirable for the decrease rate of integral strength of the lithium titanate particle group to be 25% or more. [Explanation of symbols]
[0157] A...Metal compound particle group C: Coating layer 1…Primary particle 2...Void
Claims
1. An element having a positive electrode and a negative electrode including a metal compound particle group; an electrolyte impregnated in the element; Equipped with The metal compound particle group is It has a three-dimensional network structure in which metal compound particles, which are lithium titanate particles, are connected together, The three-dimensional network structure has voids, A part of the metal compound particle group contains SiO x Or SiO x (OH) 4-2x (x is 0 to 2), a coating layer containing silicon oxide is formed, The coating layer containing the silicon oxide is formed on the outer peripheral surfaces of the metal compound particle group and on the surfaces of the voids, but is not formed so as to fill the voids, The content of the Si element is 0.4 to 3.0 wt % based on the total weight of the metal compound particle group; The power storage device is characterized by:
2. 2. The electricity storage device according to claim 1, wherein the silicon oxide contained in the coating layer is an amorphous silicon oxide.
3. The metal compound particle group is a pore volume change rate converted from a pore distribution measured by a nitrogen gas adsorption measurement method, and is 0.008 dV for a pore diameter of 10 nm or less. p / dr p The electricity storage device according to claim 1 or 2, having a pore volume change rate of more than 1000 μm.
4. A solid is added to the metal compound particles on which the coating layer containing silicon oxide is not formed. 1 4. The electricity storage device according to claim 1, wherein a reduction rate of integrated intensity of a peak present at 5 to 8 ppm among peaks obtained by H-NMR is 25% or more.
5. The electricity storage device according to claim 1 , wherein the electrolyte contains a fluorine-containing compound.
6. A mixing step of mixing a group of metal compound particles as a base with a raw material of silicon oxide; a heating step of heating the powder obtained by the mixing step at 300 to 600°C; Including, a pretreatment step of pretreating the base metal compound particle group with an alkali compound prior to the mixing step, In the mixing step, the silicon oxide raw material is mixed in a ratio of 1 to 20 wt % with respect to the weight of the base metal compound particle group, the base metal compound particle group is a lithium titanate particle group having a three-dimensional network structure with voids, The alkali compound is a compound containing an alkali metal or an alkaline earth metal. A method for producing metal compound particle groups.
7. 7. The method for producing metal compound particle groups according to claim 6, wherein the silicon oxide raw material is mixed in a ratio of 3 to 20 wt % based on the weight of the metal compound particle groups as a base.
8. 8. The method for producing a metal compound particle group according to claim 6, wherein one or more kinds of the alkali compound are further mixed in the pretreatment step.
Citation Information
Patent Citations
Lithium-transition metal complex oxide powder and method for manufacturing the same, and positive electrode active material for all-solid lithium battery using the powder
JP2012199101A
Positive electrode for all-solid type lithium secondary batteries, and all-solid type lithium secondary battery arranged by use thereof
JP2015185237A
All-solid battery
JP2015185337A
Manganese dioxide for production of lithium manganate, and production method thereof
JP2015189608A
Method for producing surface-treated oxide particles, and oxide particles produced by said production method
WO2015072359A1